The methodological essence of training primary school teachers in their interconnected educational and foreign language professional activities - Frumkina Aryna (Науковий Вісник Південноукраїнського Національного Педагогічного Університету імені К. Д. Ушинського, 2019)
The article highlights the problems related to the training of the primary school teachers in their interconnected educational and foreign language professional activities. It is stated that training of future primary school teachers cannot consist only in teaching isolated subject content, but it should be carried out on the basis of the formation of several types of competencies, such as: psychological and pedagogical, major subject-centred, methodology-oriented. The combination of these competencies will lead future teachers to their readiness to teach schoolchildren any of the curriculum subjects. The aim of the work is to substantiate the possibility of developing the readiness of primary school teachers for integrated teaching educational and foreign language speech activities using the example of teaching Fine Arts in English. An attempt to substantiate this action is supposed to be based on the laws of dialectics, namely: the law of unity and diversity of the world, the law of unity and struggle of opposites, the law of the transition of quantitative changes to qualitative ones, the law of the negation of negation, which are considered the main driving forces for the development of nature, society and intelligence. The research methods are as follows: theoretical – the analysis of pedagogical, psychological, didactic literature on the research problem, which allows further theoretical substantiation of the expediency of the training intended for the future Primary School teachers for integrated teaching educational and foreign language speech activities. Taking into account the results of the work, we came to the conclusion that it can be considered dialectically legitimate for the future Primary School teachers to integrate teaching an educational course in a foreign language, during which primary schoolers obtain knowledge and develop skills in their major subject, as well as foreign language knowledge, skills and abilities, allowing both to learn the basic discipline by means of a foreign language, and to conduct educational activities at the lesson by means of a foreign language.